2018
DOI: 10.3389/fpsyg.2018.02069
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership as Antecedent of Job Satisfaction, Affective Organizational Commitment and Intention to Stay Among Volunteers of Non-profit Organizations

Abstract: The aim of this paper is to investigate among a group of non-profit organizations: (a) the effect of ethical leadership (EL) on volunteers’ satisfaction, affective organizational commitment and intention to stay in the same organization; (b) the role played by job satisfaction as a mediator in the relationship between EL and volunteers’ intentions to stay in the same organization, as well as between EL and affective commitment. An anonymous questionnaire was individually administered to 198 Italian volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 151 publications
(187 reference statements)
9
64
0
2
Order By: Relevance
“…The results also extend research on ethical leadership in different ways. First, this study confirms that, as already observed in the literature, the ethical leadership construct is related to work engagement (Ahmad & Gao, ; Asif et al, ), job satisfaction (Benevene et al, ; Qing, Asif, Hussain, & Jameel, in press) and leader–member exchange (Walumbwa et al, ), extending the existence of these associations to a health care setting. In particular, the positive relationship with leader–member exchange confirms that ethical leadership, although different, shares some characteristics with other leadership styles, which in this case is the positive orientation towards employees in order to share and implement moral and ethical behaviours (Den Hartog, ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results also extend research on ethical leadership in different ways. First, this study confirms that, as already observed in the literature, the ethical leadership construct is related to work engagement (Ahmad & Gao, ; Asif et al, ), job satisfaction (Benevene et al, ; Qing, Asif, Hussain, & Jameel, in press) and leader–member exchange (Walumbwa et al, ), extending the existence of these associations to a health care setting. In particular, the positive relationship with leader–member exchange confirms that ethical leadership, although different, shares some characteristics with other leadership styles, which in this case is the positive orientation towards employees in order to share and implement moral and ethical behaviours (Den Hartog, ).…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the effects of ethical leadership, the literature suggests that they are related, among others, to an enhanced sense of meaning and well‐being in the workplace (Avey, Wernsing, & Palanski, ), organisational commitment to the organisation (Lotfi, Atashzadeh‐Shoorideh, Mohtashami, & Nasiri, ; Neves & Story, ), trust in organisations (Xu, Loi, & Ngo, ), and organisational ethical climate (Demirtas & Akdogan, ; Treviño et al, ). Furthermore, ethical leadership seems to be positively associated with work engagement (Ahmad & Gao, ; Asif, Qing, Hwang, & Shi, ), job satisfaction (Benevene et al, ; Qing, Asif, Hussain, & Jameel, in press) and leader–member exchange (Walumbwa et al, ), and it seems to be negatively associated with employee burnout (Mo & Shi, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as with other organizational variables, there are few studies that address the relationship between volunteer coordinators' leadership style and volunteers' retention (Smith, 2017). Extant studies also focus on very specific leadership styles: ethical leadership (Benevene et al, 2018), autonomy-supportive leadership (Oostlander et al, 2014), and servant leadership (Hines, 2017;Schneider & George, 2011).…”
Section: Direct Effects Of Transformational Leadership On Volunteers'mentioning
confidence: 99%
“…In turnover research, work attitudes have been frequently investigated; for example, job satisfaction and organizational commitment have been reported to be connected to quality nursing performance and job retention (Ahmad, Ahmad, & Shah, ; Halter et al, ). Nurses who are satisfied with their tasks, their work environments and the ways they are treated by their organizations are likely to feel a deeper connection to their organizations and accordingly increase their organizational commitment (Benevene et al, ; Chang, ). In contrast, low levels of job satisfaction and organizational commitment have been linked to negative work outcomes, such as missed nursing care, poor‐quality nursing care, decreased organizational citizenship behaviour and high turnover (Gillet et al, ; Rose, ).…”
Section: Introductionmentioning
confidence: 99%